2005
DOI: 10.1002/dmrr.598
|View full text |Cite
|
Sign up to set email alerts
|

Pulse pressure and mortality in hypertensive type 2 diabetic patients. A cohort study

Abstract: High PP, assessed through office measurement or ABPM, was associated with increased mortality in hypertensive type 2 diabetic patients. In our sample, PP assessed with ABPM is a better predictor of mortality than office PP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 11 publications
0
24
0
Order By: Relevance
“…In keeping with our current observations, there was no significant interaction between the presence of diabetes and the 24-h systolic BP. 29 Several studies, [30][31][32] including a previous report from the IDACO consortium, 3 confirmed that the ambulatory BP is a better predictor of cardiovascular risk than Figure 2 10-year absolute risk of the composite cardiovascular end point associated with the 24-h systolic (a) and diastolic (b) blood pressures in patients with diabetes and non-diabetic subjects. The analysis was standardized to the distributions (mean or ratio) of cohort, age, sex, body mass index, smoking and drinking, treatment with antihypertensive drugs, history of cardiovascular disease and total serum cholesterol, and included an interaction term for diabetes and blood pressure.…”
Section: Discussionmentioning
confidence: 93%
“…In keeping with our current observations, there was no significant interaction between the presence of diabetes and the 24-h systolic BP. 29 Several studies, [30][31][32] including a previous report from the IDACO consortium, 3 confirmed that the ambulatory BP is a better predictor of cardiovascular risk than Figure 2 10-year absolute risk of the composite cardiovascular end point associated with the 24-h systolic (a) and diastolic (b) blood pressures in patients with diabetes and non-diabetic subjects. The analysis was standardized to the distributions (mean or ratio) of cohort, age, sex, body mass index, smoking and drinking, treatment with antihypertensive drugs, history of cardiovascular disease and total serum cholesterol, and included an interaction term for diabetes and blood pressure.…”
Section: Discussionmentioning
confidence: 93%
“…There have been a few studies in diabetes patients, showing associations of ABP with cardiovascular outcomes 26 and all-cause mortality, 19,27 but they had significant limitations: in one study ABPM was performed in a hospital setting; 26 in another the study design was retrospective and the number of patients was small; 19 and in the third only clinic and ambulatory pulse pressures were used in the analysis, and the contributions of ambulatory awake/sleep pulse pressures and of ambulatory SBPs and DBPs were not analyzed. 27 As a result, the utility of ABPM in patients with diabetes is not yet accepted. In our study, although clinic SBP predicted Values are hazard ratios (95% confidence interval), per 10 mm Hg difference in SBP.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16] However, only a few BP parameters were evaluated in each of these studies and the potential interaction between BP parameters were not examined. Moreover, some studies report the association with total mortality, not with CV mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some studies report the association with total mortality, not with CV mortality. 10,11 In addition, the general applicability of some of the reported associations is limited owing to methodological characteristics of the individual studies, as they are either cross-sectional; 12 the study-populations consist of older patients with a long duration of diabetes; 13,14 ABPM was performed in hospitalised patients 15 or in a mixed cohort of type 1 and 2 diabetes patients. 16 Hence, despite these previous studies, several questions remain unresolved, particularly if 24-h PP, AASI and diurnal BP parameters obtained from ambulatory measurement in the early course of the disease predict future CV events above other BP parameters, after adjustment for well-established CV risk markers.…”
Section: Introductionmentioning
confidence: 99%